"The Tragedy of the Commons": How Individualism and Collectivism Affected the Spread of the COVID-19 Pandemic - Yossi Maaravi; Aharon Levy; Tamar Gur; Dan Confino; Sandra Segal (Frontiers Media S.A., 2021)
Why did COVID-19 hit some countries harder than others? While this question is usually answered based on demographics (e. g., population age), health policy (e.g., quarantine), or economic factors, we argue that cultural variance across countries is just as crucial in understanding how susceptible a society is to the COVID-19 outbreak. To test this hypothesis, we first analyzed data collected across 69 countries and examined the relationship between culture and the impact of COVID. Next, we conducted two studies to validate our findings further and explore the mechanism at hand. As expected, we found that the more individualistic (vs. collectivistic) a country was, the more COVID-19 cases and mortalities it had. We also found that the more individualistic participants were, the higher the chances they would not adhere to epidemic prevention measures. These findings are important in understanding the spread of the pandemic, devising optimal exit strategies from lockdowns, and persuading the population to get the new vaccine against the virus.